Politisasi Kebijakan Program Marasa Ali Baal Masdar - Ramadhan, Muh Fajar (Universitas Muhammadiyah Tapanuli Selatan, 2023)
AbstractOne of the important stages in the public policy cycle is policy implementation. Implementation is often considered only as the implementation of matters that have been decided by the legislature or decision makers, as if this stage had less influence. However, in reality, the implementation stage becomes very important because a policy will be meaningless if it cannot be implemented properly and correctly. This research is a descriptive qualitative research with literature review data collection method. West Sulawesi Province as one of the youngest provinces, where there are still many villages in the underdeveloped category and some of the people are below the poverty line, especially in rural areas, so to accelerate poverty alleviation, especially in rural areas, a comprehensive way of overcoming it is needed by involving all stakeholders. interest; the Independent, Smart and Healthy Village (MARASA) program as one of the priority programs in the West Sulawesi Provincial RPJMD 2017-2022 is a program designed to streamline poverty alleviation efforts through strategic and integrated cross-sector management to achieve an independent, smart and healthy community .Keywords: MARASA, Politicization, Policy